Advertisement Remove all ads

Solve for X : 23x + 3 = 23x + 1 + 48 - Mathematics

Sum

Solve for x : 23x + 3 = 23x + 1 + 48

Advertisement Remove all ads

Solution

23x + 3 = 23x + 1 + 48
⇒ 8 x 23x = 23x x 2 + 48
⇒ 23x ( 8 - 2 ) = 48
⇒ 23x x 6  = 48
⇒ 23x = 8
⇒ 23x = 23
⇒ 3x = 3
⇒ x = 1

Concept: Solving Exponential Equations
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Selina Concise Mathematics Class 9 ICSE
Chapter 7 Indices (Exponents)
Exercise 7 (B) | Q 14.4 | Page 101
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×